Organic entities, costume, human body and neo-liberalism. Issue 1 (1st June 2021) - Kolenik, Tina
This visual essay presents four of the author's artistic projects, which respond to prevailing eastern European neo-liberal conceptions of the human body and the subjects it produces. The first project is concerned with the use of human skin as an organic material donated by its 'owner' for the manufacture of a corset and belt, which become parts of a new costume. The second project explores the characteristic of the 'ideal' neo-liberal human subject by means of the costume produced by manipulating the author's own blood. The third project highlights the cultural norm according to which one is expected to present oneself to the known and especially unknown others in line with the dominant standards of feminine beauty ‐ erotically attractive, healthy, youthful and slim. The fourth project focuses on the almost obsessive endeavour to preserve or rather achieve 'the perfect skin', as evident in countless beauty advertisements and artificially 'optimized' selfies.